EMPOWERING MINDS: THE ROLE OF TEACHER QUESTIONING IN PROMOTING CRITICAL LITERACY IN LANGUAGE CLASSROOMS - Febrianingrum, Lasmi; Mustofa, Ali (Universitas Muhammadiyah Makassar, 2025)
In recent years, there has been growing recognition of the pivotal role that teacher discourse plays in shaping students’ critical engagement with texts. Within this context, this study investigates how teacher questioning strategies foster critical literacy in language classrooms. Through analysis of theoretical frameworks and empirical research, the study examines the effectiveness of various questioning techniques in developing students' critical thinking abilities. The findings demonstrate that structured questioning frameworks, particularly those incorporating higher-order thinking skills, enhance students' analytical capabilities and text engagement. Additionally, culturally responsive questioning approaches create more inclusive learning environments and empower marginalized voices. These insights inform recommendations for teacher training programs and classroom practices to promote critical literacy through effective questioning strategies.